Predictors of intention to use reusable drinking straw: A case study in Selangor / Shahariah Asmuni, Sabariah Yusoff and Nur Liyana Asyiqin Mohd Jafri - Asmuni, Shahariah; Yusoff, Sabariah; Mohd Jafri, Nur Liyana Asyiqin (Universiti Teknologi MARA, 2021)
Single-use plastic drinking straws is difficult to recycle and is one of the main causes of water pollution and marine animal destruction. An option for single use drinking straws is reusable ones. This study applies the theory of planned behavior (TPB) to determine the factors affecting the intention to use reusable drinking straw using a survey method in Selangor, Malaysia. Based on an OLS multiple regression result, the study concluded that attitude and perceived behavioral control are significant predictors for the intention to use reusable drinking straws. Government campaigns towards encouraging consumers to use reusable drinking straws should be focused on promoting positive aspects reusable drinking straws and make it accessible and plausible for the consumers to use it.